Some Social Aspects of the Soul of Multiverse Hypothesis: Human Societies and the Soul of Multiverse - Ludvig, Nandor (Journal of NeuroPhilosophy, 2023)
As a continuation of this author’s previous cosmological neuroscience papers on the hypothesized Soul of Multiverse and its possible laws, the present work examined the social aspects of four of these laws. The following key aspects were recognized: (1) Knowing about the cosmic Law of Coexistence in Diversity can let our mind respect not only the endless diversity of human beings but also the cohesive force of space-time in which all are connected. This may help realizing the superiority of cooperation for shared goals over competition for gaining by harming others. (2) Knowing about the cosmic Law of Truth in Complexity can ready our mind to confront the problems of societies with the understanding that these problems are much more complex than generally thought. This may help initiating the needed intellectual renaissance of the 21st century. (3) Knowing about the cosmic Law of Divine - Evil Asymmetry can make our mind appreciate the slight yet sufficient supremacy of divine over evil. This may help restoring faith in the eventual creation of a just society, where social justice is defined as an administrative mechanism providing the right conditions for every human being to accomplish his or her Conscience-led Mission throughout life, while allowing each of these accomplishments to be reciprocated with the gratitude it induced in the involved social systems, small or large, to let equal opportunities in life coexist with due diversity in welcomed, not abused, social recognitions. And (4) knowing about the cosmic Law of Lives to Transcend can empower our mind to build on these advances. This may help moving evolution towards the human species worthy of its origin and destination.